Simulation of Coastal Processes affecting pH with Impacts on Carbon and Nutrient Biogeochemistry - KAPETANAKI, NATALIA; KRASAKOPOULOU, EVANGELIA; STATHOPOULOU, ELENI; PAVLIDOU, ALEXANDRA; ZERVOUDAKI, SOULTANA; DASSENAKIS, MANOS; SCOULLOS, MICHAEL (Mediterranean Marine Science, 2018)
Naturally occurring microbial decomposition of organic matter (OM) in coastal marine environments cause increased acidity in deeper layers similar or even exceeding the future predictions for global ocean acidification (OA). Experimental studies in coastal areas characterized by increased inputs of OM and nutrients, coping with intermittent hypoxic/anoxic conditions, provide better understanding of the mechanisms affecting nutrients and carbon biogeochemistry under the emerging effects of coastal pH decrease. Laboratory CO2-manipulated microcosm experiments were conducted using seawater and surface sediment collected from the deepest part of Elefsis Bay (Saronikos Gulf, Eastern Mediterranean) focusing to study the co-evolution of processes affected by the decline of dissolved oxygen and pH induced by (a) OM remineralization and (b) the future anthropogenic increase of atmospheric CO2. Under more acidified conditions, a significant increase of total alkalinity was observed partially attributed to the sedimentary carbonate dissolution and the reactive nitrogen species shift towards ammonium. Νitrate and nitrite decline, in parallel with ammonium increase, demonstrated a deceleration of ammonium oxidation processes along with decrease in nitrate production. The decreased DIN:DIP ratio, the prevalence of organic nutrient species against the inorganic ones, the observations of constrained DON degradation and nitrate production decline and the higher DOC concentrations revealed the possible inhibition of OM decomposition under lower pH values. Finally, our results highlight the need for detailed studies of the carbonate system in coastal areas dominated by hypoxic/anoxic conditions, accompanied by other biogeochemical parameters and properly designed experiments to elucidate the processes sequence or alterations due to pH reduction.